Bidirectional Quantum Secure Direct Communication Using Dense Coding of Four Qubit Cluster States - Chauhan, S.; Gupta, N. L. (Journal of Scientific Research, 2022)
We are introducing an efficient bidirectional quantum secure direct communication protocol that employs the four qubit cluster states, creating a novel quantum channel based on dense coding between the transmitter and receiver. By dense coding, after a conventional announcement, two legitimate users can simultaneously exchange their messages. Two safety checking measures are taken to ensure safe transmission. Information leaking is not an issue in this protocol, and it is secure against some well-known eavesdropping assaults. It is also accessible with cutting-edge technology.